2014
DOI: 10.1111/asj.12306
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐independent actions of glucagon‐like peptide‐1 in wethers

Abstract: Insulin-independent actions of glucagon-like peptide-1 (GLP-1) are not yet clear in ruminants. Four Suffolk mature wethers (60.0 ± 6.7 kg body weight (BW)) were intravenously infused with insulin (0.5 mU/kg BW/min; from 0 to 90 min) and GLP-1 (0.5 μg/kg BW/min; from 60 to 150 min) with both hormones co-administered from 60 to 90 min, in a repeated-measure design under euglycemic clamp for 150 min, to investigate whether GLP-1 has insulin-independent actions. Jugular blood samples were taken at 15-min intervals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…However, in our study the plasma insulin concentrations were kept constant by GLP‐1 infusion (El‐Sabagh et al . ), indicating a direct action of GLP‐1 on protein metabolism with no significant contribution of insulin. Also, it was reported that GLP‐1 exerts a protective effect against hepatocellular injuries (Klonoff et al .…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…However, in our study the plasma insulin concentrations were kept constant by GLP‐1 infusion (El‐Sabagh et al . ), indicating a direct action of GLP‐1 on protein metabolism with no significant contribution of insulin. Also, it was reported that GLP‐1 exerts a protective effect against hepatocellular injuries (Klonoff et al .…”
Section: Discussionmentioning
confidence: 97%
“…These results are consistent with changes in blood profile reported in our previous publication (El‐Sabagh et al . ) where plasma concentrations of NEFA, BHBA and triglyceride were raised, but total cholesterol was decreased by GLP‐1 infusion. These results may suggest a physiological role for GLP‐1 in inducing lipid mobilization and oxidation, and this situation may be associated with ketogenesis and accumulation of cholesterol and sterols in liver.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations